"Better but not best": a qualitative exploration of the experiences of occupational gain for people with inflammatory arthritis receiving anti-TNFα treatment. (May 2015) - McArthur, Margaret A.; Birt, Linda; Goodacre, Lynne
Abstract Objectives: To investigate whether patients with improved clinical markers during their anti-TNFα treatment experience improvements in their functional and psychological ability to undertake activities. Methods: Patients receiving anti-TNFα treatment for rheumatoid arthritis (RA) or ankylosing spondylitis (AS) were recruited from outpatient clinics in East Anglia and North West England. Purposive sampling recruited variety in demographic and treatment experiences. Data were collected through in-depth qualitative interviews and analysed using an interpretive phenomenological framework. Twenty-seven patients were recruited; 19 with RA, eight with AS, and aged from 21 to 73 years. Results: While people generally experienced an improvement in their functional ability, known as occupational gain, they continued to experience difficulties through previous biomechanical damage, continuing symptoms of inflammatory arthritis, or concerns about anti-TNFα treatment. These disruptions affected how participants retained or regained employment. Lack of healthcare support, including an absence of occupational therapy intervention, resulted in people testing new boundaries through a process of unsupported trial and error. Conclusion: Occupational gain was not maximised for people on anti-TNFα treatment. Improved referral pathways to occupational therapy could facilitate the management of continuing functional difficulties, thereby maximising the benefit of treatment to people with inflammatory arthritis. Implications for Rehabilitation This study challenges the assumption that functional improvement for people with rheumatoid arthritis (RA) and ankylosing spondylitis (AS) receiving anti-TNF a treatment experience is relatively trouble-free. Rheumatology provision needs to be more closely informed by and aligned with the needs of these service users to maximise the benefit from what is an expensive treatment option. People with RA and AS would both benefit from more focused occupational therapy interventions addressing the impact of occupational performance on occupational engagement.